2020
DOI: 10.1002/aisy.202000071
|View full text |Cite
|
Sign up to set email alerts
|

Robotics, Smart Wearable Technologies, and Autonomous Intelligent Systems for Healthcare During the COVID‐19 Pandemic: An Analysis of the State of the Art and Future Vision

Abstract: Herein, how robotic and autonomous systems and smart wearables complement and support healthcare delivery and the healthcare staff during the COVID‐19 pandemic are presented. For instance, robotic and telerobotic systems significantly reduce the risk of infectious disease transmission to frontline healthcare workers by making it possible to triage, evaluate, monitor, and treat patients from a safe distance. Various examples of where the medical, engineering, and science communities come together to aid the hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
165
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(185 citation statements)
references
References 5 publications
0
165
0
2
Order By: Relevance
“…To summarize, AI and robotics could play an important role in providing telemedicine services during an outbreak or public health emergency while limiting exposure to healthcare workers and health systems (14,42,43). The AI-assisted telemedicine framework proposed by the current consortium could be an enabler in improving telemedicine access and spread across medical specialties and geography.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To summarize, AI and robotics could play an important role in providing telemedicine services during an outbreak or public health emergency while limiting exposure to healthcare workers and health systems (14,42,43). The AI-assisted telemedicine framework proposed by the current consortium could be an enabler in improving telemedicine access and spread across medical specialties and geography.…”
Section: Resultsmentioning
confidence: 99%
“…Robotics is a promising cutting-edge tool in telemedicine that has potential applications in transforming physical exam and clinical care, as well as monitoring patients in remote conditions (42,43). Such experience with the Ebola outbreak and with the COVID-19 pandemic has revealed a wide range of robotic uses and telemedicine options (43,44).…”
Section: Robotics Assisted Telemedicinementioning
confidence: 99%
See 1 more Smart Citation
“…The current COVID-19 pandemic brings along several threats and restrictions to our society. A variety of potential implementations have been proposed to utilize robots in healthcare and beyond to face these challenges 11,12 . Healthcare workers are at the battle's forefront during pandemics and a professional group with high vulnerability.…”
Section: Robotic Technology In the Age Of Pandemicsmentioning
confidence: 99%
“…In case a hospital visit is required, it must be scheduled carefully to provide safe passage for the patient. Artificial intelligence‐based online screening tools and medical robotic assistant can be used for initial screening for signs and symptoms of COVID‐19, and patients can be advised to have a COVID‐19 test prior to the dental appointment 16–18 . It is suggested that the oral cavity can be cleaned in dental operatory with cotton gauze dipped in chlorhexidine or povidone‐iodine if the patient is unable to perform pre‐procedural mouth rinses 7 .…”
mentioning
confidence: 99%